Effects of Leucaena (Leucaena leucocephala) as Roughage Source on Goat Performance and Economic Worthiness - สือแม ซารีนา; ไกรพรม เทียนทิพย์ (Princess of Naradhiwas University Journal, 2018)
This study aimed to identify the effects of using leucaena (Leucaena leucocephala) as a roughage source on male goat production (50% Thai native, 50% X Anglonubian) and economic worthiness. The experimental design was completely randomized with 3 treatments and 5 replications, namely, the goats ingested 100% signal grass (Brachiaria humidicola) in control group, while the goats ingested 50% leucaena combined with 50% grass, and 100% leucaena as roughage source in the other groups, respectively. All goats were fed 2% BW of the concentrate meal. The results found that the leucaena had significantly affected goat production performance. Goats fed with 100% of leucaena gained heavier weight (6.00 kg/h) than the control group (3.75 kg/h) and goat fed 50% leucaena combined with 50% grass (4.25 kg/h). The growth rate (66.67 g/h/d) of goat received 100% leucaena was significantly higher (P<0.05) than both other groups. Digestibility rates for the goats treated with 50% leucaena and 50% grass were significantly higher (P<0.05 CP digestibility, 82.44%) than in the control group (74.82%), when goats fed with 100% leucaena yielded a value of 85.03%. Furthermore, the economic value in goat fed with 100% leucaena (431.84 Baht/h) was the highest. In summary, the use of 100% of leucaena as roughage source gave considerable effect on goat production performance and CP digestibility without negative effect on voluntary intake of goat and also potentially generated the highest economic worthiness.